(untitled) (Global Journal of Medical Research, 2020)
Determining animal growth and physiological parameters, their inter-relationship and correlation with various haemato-biochemical and mineral profile during summer and winter seasons in present climatic conditions are imperative for defining genetic potential and adaptation of black Bengal breed for higher meat production. The recorded body weight was found positively correlated with (P ≤ 0.01) height, heart girth and, linear length during both summer and winter season, indicating that they can be used to estimate body weight in black Bengal goats of different ages under field conditions where scales are not usually available. The pulse rate was found to be negatively correlated with (P ≤ 0.01) body weight during both the summer and winter season. Total erythrocyte count (TEC) was negatively correlated (P ≤ 0.05) with the weight during summer but positively (P ≤ 0.01) during the winter season.